2015
DOI: 10.1007/s00168-014-0655-8
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in peripheral regions: Do collaborations compensate for a lack of local knowledge spillovers?

Abstract: It is widely accepted that firms in peripheral regions benefit to a lesser extent from local knowledge spillovers than firms located in agglomerations or industrial clusters. This paper investigates the extent to which innovative firms in peripheral regions compensate for the lack of access to local knowledge spillovers by collaborating at other geographical scales.So far the literature predominantly suggests that collaborations complement rather than compensate for local knowledge spillovers. Using data on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
183
0
13

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(208 citation statements)
references
References 57 publications
12
183
0
13
Order By: Relevance
“…Path changes are in general triggered by the presence of a broad variety of firms and knowledge bases in a region (Frenken et al 2007), conditions that are usually not found in thin RISs. Firms in thin RISs can compensate for a scarce local knowledge supply base by internalising some of the resources that are missing in the local business environment (Isaksen 2015), and by entering into distant collaboration networks (Grillitsch and Nilsson 2015). The first strategy may not lead to more than path extension if firms build up internal resources (e.g.…”
Section: Development Challenges and Policy Approaches In Regions Withmentioning
confidence: 99%
“…Path changes are in general triggered by the presence of a broad variety of firms and knowledge bases in a region (Frenken et al 2007), conditions that are usually not found in thin RISs. Firms in thin RISs can compensate for a scarce local knowledge supply base by internalising some of the resources that are missing in the local business environment (Isaksen 2015), and by entering into distant collaboration networks (Grillitsch and Nilsson 2015). The first strategy may not lead to more than path extension if firms build up internal resources (e.g.…”
Section: Development Challenges and Policy Approaches In Regions Withmentioning
confidence: 99%
“…Only a few studies have focused on linkages between urban and rural areas, yet with a focus on innovation and knowledge sources [44,45], and in some cases with a deficiency perspective. Indeed, Grillitsch and Nilsson [46] show that firms in peripheral areas often use external linkages as compensation for insufficient local exchange. A focus on the complementarity of rural-urban linkages with competencies that already exist in the rural context is missing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fitjar and Huber [47] show, for the case of Norway, that innovative firms have more international linkages than less innovative firms. For Swedish firms in peripheral regions, Grillitsch and Nilsson [46] conclude that firms in the periphery use external linkages more often than firms in core regions, which implies that they are more important than local links in the peripheral context. Cabiddu and Petinao [45] illustrate for a food processing company in the Ogliastra region of Sardinia how external linkages can strengthen the firm's absorptive capacity and thus its competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although it is questionable how innovation plays a role in the above process, the case of Portugal shows us that the lack of innovation hinders the chance for long run convergence [56]. Other examples from peripheral areas including New Zealand [15], Norway [20] and Sweden [19] highlight the importance of interregional and international collaboration. Because the innovation infrastructure is poorly developed in CEE locations, innovative firms build extensively on sources located elsewhere and thus, are more active in interregional and international collaboration.…”
Section: Discussionmentioning
confidence: 99%